Characteristics and changes in invasive meningococcal disease epidemiology in France, 2006–2015. Issue 6 (June 2017) - Parent du Chatelet, I.; Deghmane, A.E.; Antona, D.; Hong, E.; Fonteneau, L.; Taha, M.K.; Lévy-Bruhl, D.
Summary: Objectives: This work aimed to describe the epidemiology of invasive meningococcal disease (IMD) in France, 2006–2015, including group- and genotype-specific disease burden, incidence trends before and after introduction of meningococcal C conjugate vaccines (MCCV) in 2010, and factors influencing the case fatality rate. Methods: Mandatory notification data on incidence and IMD case characteristics were used. Genotyping of invasive strains and whole genome sequencing were performed by the French National Reference Center. Vaccination coverage was estimated from the National Health Insurance Information System's reimbursement data. Results: The decrease in annual IMD incidence rates (per 100, 000 inhabitants) from 1.23 in 2006 to 0.78 in 2016 was mainly related to the decrease in group B IMD. Group C incidence decreased from 0.29 in 2006 to 0.13 in 2010 but increased thereafter in age groups not targeted by MCCV. From 2010 onwards, MCCV coverage gradually increased but remained below 25% in 15–19 year-olds in 2015. Age, clinical presentation and, to a lesser extent, clonal complex 11 were the most significant factors determining mortality. Conclusions: The limited impact of vaccination on group C IMD incidence may be explained by the emergence of a new epidemic cycle in 2011 and the low vaccination coverage rates among adolescents and young adults. Highlights: In France, invasive meningococcal diseases incidence has been decreasing in the last ten years. This decrease is mainly due to decrease in group B diseases, accounting in average during for about two thirds of cases. Vaccination had a limited impact on the epidemiology of group C meningococcal diseases due to insufficient vaccine coverage. Cases due to strains belonging to the clonal complex 11 have experienced a higher risk of death.